CORRELATION OF ADDUCTOR METACARPOPHALANGEAL SESAMOID OSSIFICATION STAGES WITH DENTOFACIAL PROFILE CHANGES - Bakerly, Samira Diar; Saleh, Fayez (European Scientific Journal, ESJ, 2013)
This study aimed to correlate facial growth velocity of certain parameters with ossification stages of adductor metacarpophalangeal sesamoid as a maturity indicator. 59 mixed longitudinal lateral cephalograms and left hand-wrist radiographs for Lebanese school children (Males 23, females 23) between 9 and 15 years of age were randomly selected from the records of the out-patient clinic of the Faculty of Dentistry at Beirut Arab University. Participants have had acceptable facial profile and class I skeletal relationship. The collected data were tabulated and statistically analyzed; one way analysis of variance (1- way Anova) was performed to detect the level of significant changes in facial profile parameters with respect to ossification stages. Pearson correlation test was employed to determine whether significant differences were present between the craniofacial profile parameters and ossification stages of adductor sesamoid for males and females. The results revealed that not all the parameters measured showed correlation with the adductor sesamoid ossification stages (P < 0.05) significance level, the mandibular dimensions (Ar-Go) (r=0.758) females, (r=0.655) for males & (S-Gn) (r=0.687) males, (r=0.518) females showed the highest correlation with ossification of the adductor sesamoid at stage 3; thus if adductor sesamoid is not ossified, mandibular growth is still to come.